PROBLEMS IN EDUCATION DEVELOPMENT AND FACTORS AFFECTING IT - Poyonova Nasriddin kizi, Aziza (THE INNOVATION ECONOMY, 2025)
Currently, digital education occupies an incomparable place in the education system of our country, facilitating the education of students by creating modern conditions. The introduction of digital technologies into the education system plays a major role in the modernization of the education system of our country. This serves to improve the organization and efficiency of education